Peningkatan Kapasitas Pengelolaan Keuangan UMKM melalui Pelatihan Akuntansi Keuangan Tersistematis - Nay, Yustina Alfira; Magdalena, Christiana; Panie, Alexsandro Arsol; Baso, Susana Purnamasari; Malut, Maria Goreti; Indrawati, Agnes Susanti; Irayanti Seran, Adiutrix Maria; Betu, Kristina Wada; Suninono, Alfonsus Rodrigues; Bau Mau, Ignatia Thomasita; Bribin Burin, Stefanie Noviega; Saru, Joaquina Felicia; Goetha, Selfiana; Firmansyah, Mariano (Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service Program (PKM) activity aims to improve partners' understanding of simple accounting systems, provide financial record-keeping training, and enhance partners' capacity to produce profit and loss reports. This activity is carried out in a participatory and applicative manner, prioritizing active partner involvement in all stages of the activity. The implementation method are Identification and Analysis of Partner Needs; Design of Training Materials and Modules; Implementation of Training and Mentoring; Monitoring, Evaluation, and Follow-up Plans. The results of the activity show that: The majority of MSMEs in the informal sector have minimal financial literacy and have not yet implemented basic accounting principles; Participants enthusiastically participated in the interactive training sessions; The impact of this mentoring is not only on the technical aspects of recording, but also on changing partners' mindsets regarding the importance of business accountability. Partners are more confident in making stock purchasing decisions, because they have real data; Partners still need similar training activities in the future.